Análise do desempenho de condicionadores experimentais no tratamento de ligas metálicas - Azevedo, Eduardo Costa de (2007)
The aim of this study was to investigate the performance of three experimental surface conditioners on metal alloys of different chemical composition, through microshear tests and failure analysis. Three metal alloys (NiCr, AgPd, AgAu) were melted in disc-shaped specimens (3mm in thickness x 10mm in diameter) and their surfaces were polished with aluminum oxide abrasive papers (400-, 600- and 1200-grit). The groups were treated with one of the experimental surface conditioners, and a commercial material (Alloy Primer Kuraray) was used as a control. The bonding agent of the Adper Scotchbond system (3M) was applied, and cylindrical specimens were made with a resin cement (Rely X ARC 3M), with an adhesion area of 1.13mm2. The bonding agent and the cement were light-activated for 40s (LED SDI Radii® - 1400mW/cm2). The micro-shear test was conducted at a cross-head speed of 0.5mm/min. Bond strength values were calculated in MPa (N/mm2) and submitted to ANOVA and Tukey s post-hoc test (p<0.05). Fractographic analyzes were performed under optical microscopy (40X) and classified as adhesive, mixed or cohesive. The experimental surface conditioners did not present a satisfactory performance factor due to the means variation in the metal alloys used in the study. A predominance of adhesive failures was detected. In conclusion, the experimental surface conditioners presented a significant adhesion to all metal alloys. However, these materials need modifications to obtain values more approximate to the commercial material